Antecedents of Firm’s Performance: A Conceptual Model - Hailiang, Liu; Ramzani, Sara Ravan; Long, Hou Cheng (International Journal of Emerging Trends in Social Sciences, 2020)
This paper has been remained as evidence from the creative industry of China where it builds a conceptual framework on antecedents of organizational performance. A systematic literature review was conducted to study the possible antecedents of the performance. It found a number of factors that affect the performance of the creative Chinese industry; the major focus was on absorptive capacity, entrepreneurial orientation and market orientation. The study provides a conceptual framework, to elaborate the combination with a significant effect on performance of the firms and it is a unique contribution to literature and practice.